Secagem como estratégia para redução de perdas no pós-colheita de frutas e hortaliças: uma revisão - Pinheiro, Caroline Carvalho (Universidade Federal de São Carlos, 2026)
Fruits and vegetables are highly perishable due to the continuation of metabolic activity after harvest, particularly cellular respiration, combined with their high water content, factors that contribute to significant postharvest losses. In this context, drying stands out as an important preservation strategy by reducing water activity, increasing the commercial stability of foods, and extending their shelf life. This study aimed to conduct a literature review on the application of drying as a preservation technology to reduce postharvest losses in fruits and vegetables. The review addressed the principles of the drying process, heat and mass transfer mechanisms, drying kinetics, and the different drying techniques used in the food industry, including natural drying, tray drying, drum drying, spray drying, infrared drying, and freeze-drying. Scientific articles, books, dissertations, and theses retrieved from national and international databases were used to develop the study. In addition, case studies related to the different drying techniques were analyzed, highlighting the operating conditions, equipment used, and the main results observed for each process. The analysis demonstrated that the choice of drying technique and operating conditions directly influences the final product quality, stability, and preservation of bioactive compounds. Furthermore, these technologies showed great potential for the valorization of agro-industrial residues and the reduction of food waste. Therefore, drying is an important preservation tool, contributing to the reduction of postharvest losses and to the development of products with greater stability and extended shelf life.
Drying as a strategy to reduce post-harvest losses of fruits and vegetables: a review
Keywords: Atividade de água; Cinética de secagem; Conservação de alimentos; Frutas desidratadas; Hortaliças desidratadas; Water activity; Drying kinetics; Food preservation; Dried fruits; Dried vegetables; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS::APROVEITAMENTO DE SUBPRODUTOS; 2. Fome Zero e Agricultura Sustentável; 12. Consumo e Produção Responsáveis; 13. Ação contra a Mudança Global do Clima